Estrutura do pasto e produção animal em pastagem natural sob pastoreio rotativo - Guzatto, Cristiane (2019)
Aiming to evaluate the animal and forage production of natural pasture managed under rotational grazing at two different rest intervals and the potential use of images in the characterization of field structures, this experiment was carried out at LEPAN, the spring / summer periods of 2018/2019 and lasting 194 days divided into seven periods. The experimental area was divided into two treatments considering the resting interval of the pasture, using the rotational grazing method, with the grazing intervals determined by the accumulation of daily average temperature of 375 and 750 degrees, favoring the growth of competing and resource conserving species. Twenty four Braford heifers were used, with age and initial weight of 12 months and 234 kg, respectively. The images were obtained in two moments, 23/05/2018 and 24/05/2019, in JPG format and the physical limits of the sample units were the reference criteria for georeferencing, being submitted to the classification process conducted in the QGIS Application. Sward structural variables (tussock height (cm), tussock leaf participation (%), starting and departing forage mass (FM) of the tussock stratum (Kg DM ha-1), starting and departing FM of the non tussock stratum (Kg DM ha-1)) showed no significant differences. The variables non tussock stratum height (cm), % non tussock leaf, % non tussock dead material (DM) and % tussock DM presented interaction between treatment and period. For the non tussock stratum height variable (cm) it was observed that the mean height at treatment 750 was 4.7 cm and 7.7 cm higher than at treatment 375 in periods 3 and 6, respectively. The percentage of non tussock leaf (%) was higher at the periods 1 and 2, and in both, the characteristic was higher in the treatment 375 GD (53%). The lower stratum remained similar between the images, however, the upper stratum decreased 27% in Image 2, due to the location from which the image was taken. Body weight (BW), daily weight gain (DWG), instantaneous stocking (IS) and live weight gain (LWG) did not show treatment * period interaction. The average body weight was 269 kg, being higher in the treatment 375 (275 kg). Instantaneous stocking was higher at 375 (2782 kg ha-1). In contrast, the non tussock DM (%) was higher in period 1 for the long treatment (750 DD), in which 42% more DM than the short treatment. The lower and upper strata remained similar among the paddocks, however the upper stratum showed high participation, 40.85%. The visible presence of mantilla (20.5%) is linked to pasture stage and season. It was concluded that there is a higher animal performance per area in the 375 DD treatment since the DWG did not differ between them and the stocking was higher in the smallest interval. The breeding of females in natural pasture with rotational system presents satisfactory performance, thus being a valid and low cost tool for mating heifers at 24 months. The use of images helps in the characterization of structures, facilitating the management, optimizing the processes of plant growth and forage seizure by the animal.